THE EFFECTS OF GAP SPACING RATIO ON FLOW STRUCTURE AND HEAT TRANSFER CHARACTERISTIC FOR THE V-ORIFICE IN THE SQUARE CHANNEL HEAT EXCHANGER - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2019)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Thermal fluids; Square (algebra); Heat Transfer and Boiling Studies